Jenis-jenis Pendekatan Kelompok dalam Layanan Bimbingan dan Konseling - Habsy, Bakhrudin All; Shidqah, Syafira Badhiatus; Husna, Aulia Mustafida; Asfindha, Hany (TSAQOFAH, 2024)
This research aims to understand that the types of guidance and counseling services in a group approach are needed for the implementation of guidance and counseling services. This research uses library research methods with data coming from various sources such as books, articles, journals, documents, and others. In conducting guidance and counseling, a counselor must understand the types of guidance and counseling services in a group approach. Therefore, group approach services in guidance and counseling are needed to create a sense of trust and comfort so that guidance and counseling services can be carried out optimally.